Association between omega-6 fatty acid intake and asthma in US children and adolescents - Xiaolan Zhang; Yinghui Qu; Linjun Du; Lifang Chen; Haiyan Luan; Hailan Zhou; Qiaohuan Tian (BMC, 2024)
Abstract Background Asthma is an inflammatory disease. The potential of omega-6 fatty acids to alleviate asthma symptoms through their anti-inflammatory and immunomodulatory effects has been investigated. However, the association of dietary omega-6 fatty acids in childhood and adolescent asthma remains controversial. Objective The aim of this study was to evaluate the association between dietary intake of omega-6 fatty acids and asthma in children and adolescents in the United States. Methods We conducted a cross-sectional analysis of 5045 children and adolescents from the National Health and Nutrition Examination Survey (NHANES) between 2013 and 2020. Covariates were adjusted, and multivariate logistic regression, restricted cubic splines, threshold effects, and subgroup analyses were used. Results Of the 5045 participants, 1000 (19.8%) were identified as having asthma. After adjustment for potential confounders, individuals in the second group (T2, 215.3-377.7 mg/kg/day) had an adjusted odds ratio (OR) of 0.70 (95% CI: 0.57-0.86, P = 0.001) for asthma compared with those in the lowest omega-6 fatty acid intake group (T1, < 215.3 mg/kg/day). Similarly, individuals in the third group (T3, > 377.7 mg/kg/day) had an adjusted OR of 0.59 (95% CI: 0.45-0.78, P < 0.001) for asthma. Furthermore, a non-linear (L-shaped) relationship between omega-6 intake and asthma was observed (P = 0.001), with subgroup analyses confirming the stability of the results. In the threshold analysis, a critical turning point was observed at around 384.2 mg/kg/day (OR = 0.996, 95% CI: 0.995-0.998, P < 0.001). Conclusion The consumption of omega-6 fatty acids in the diet showed an L-shaped association with asthma among children and adolescents in the United States. A critical turning point was noted at approximately 384.2 mg/kg/day.